The position of the Shiites towards the extremist Islamic currents until the end of the Abbasid era - جواد شايب (آداب الكوفة, 2015)
We touched on the position of the Shiites on extremist currents, and it is one of the largest Islamic sects, and it has strong and firm stances towards these currents, especially Ahl al-Bayt (B).